Performance of Sprayed PVDF-Al2O3 Composite Coating for Industrial and Civil Applications - Adel M. A. Mohamed (MDPI AG, 2021)
Because of their great water repellency, Superhydrophobic coatings have a major impact on a variety of industrial applications. The current study’s key originality is the development of low-cost, stable, superhydrophobic, and corrosion-resistant composite coatings. In the present work, polyvinylidene fluoride (PVDF)/Al2O3 composite coatings were produced using the spray technique to investigate the wettability and corrosion behavior of the coated materials for industrial and civil applications. PVDF was mixed with various concentrations of Al2O3 nanoparticles, and the mixture was sprayed onto steel, aluminum, and glass substrates. The wettability and morphology of the coated surfaces were investigated using the sessile droplet method and scanning electron microscopy, respectively. The corrosion resistance of bare substrates was compared to that of those coated with PVDF alone and those coated with PVDF/Al2O3 nanoparticles using Tafel polarization techniques. The force of adhesion between the coat and the substrates was measured in pounds per square inch. A nanoindentation test was also used to measure the hardness of the coating layer. The PVDF/Al2O3 coated steel showed a significantly higher water contact angle and lower contact angle hysteresis, reaching 157 ± 2° and 7 ± 1°, respectively, compared to the coated aluminum and glass substrates. Corrosion test results showed that the superhydrophobic PVDF/Al2O3 coatings had a much higher corrosion protection efficiency for steel and aluminum than that of the PVDF ones. The PVDF/Al2O3 coated substrates showed moderate but still acceptable adhesion between the coating layer and the substrates. Moreover, the PVDF/Al2O3 coatings had much better mechanical properties than the PVDF only coatings. Such type of coating could be a promising candidate for possible industrial and civil applications.